Accelerated vascular ageing after COVID-19 infection: the CARTESIAN study - Bruno, Rosa Maria; Badhwar, Smriti; Abid, Leila; Agharazii, Mohsen; Anastasio, Fabio; Bellien, Jeremy; Burghuber, Otto; Faconti, Luca; Filipovsky, Jan; Ghiadoni, Lorenzo; Giannattasio, Cristina; Hametner, Bernhard; et al. (My University, 2025)
Increasing evidence suggests that COVID-19 survivors experience long-term cardiovascular complications possibly through development of vascular damage. The study aimed to investigate whether accelerated vascular ageing occurs after COVID-19 infection, and if so, identify its determinants.
Keywords: Arterial stiffness; COVID-19; Long COVID; Sex differences; Vascular ageing